Buying Motorcycles: What Part Does the Marketing Mix Play - Tadjie, Gilang Sekar; Sudrajat, Yayat (Journal of Management, 2024)
The purpose of this study is to determine the extent to which motorcycle purchase decisions at PT. Daya Anugrah Mandiri Bandung are influenced by variables in the marketing mix. According to this study, a variety of factors influence consumers' decision to buy. From low fuel consumption, well-known brands, stylish looks, quantity and quality, limited edition models, and a host of other considerations. Additionally, it is quite challenging to pique consumers' interest in buying four-wheeled cars due to competition among marketers. Multiple linear regression is employed as an analytical tool for qualitative description, together with partial and simultaneous hypothesis testing. In this study, 45 respondents served as samples, and sampling was done using the Roscoe technique. The study's findings indicate that, according to the t test results, there isn't a positive or significant influence on any variable's ability to influence decisions made at PT. Daya Anugrah Mandiri Bandung about purchases.